A metabolite of Danshen formulae attenuates cardiac fibrosis induced by isoprenaline, via a NOX2/ROS/p38 pathway. (5th May 2015) - Yin, Qian; Lu, Haiyan; Bai, Yajun; Tian, Aiju; Yang, Qiuxiang; Wu, Jimin; Yang, Chengzhi; Fan, Tai‐Ping; Zhang, Youyi; Zheng, Xiaohui; Zheng, Xiaopu; Li, Zijian
Abstract : Background and Purpose: Cardiac fibrosis is a common feature of advanced coronary heart disease and is characteristic of heart disease. However, currently available drugs against cardiac fibrosis are still very limited. Here, we have assessed the role of isopropyl 3‐(3, 4‐dihydroxyphenyl)‐2‐hydroxylpropanoate (IDHP), a new metabolite of Danshen Dripping Pills, in cardiac fibrosis mediated by the β‐adrenoceptor agonist, isoprenaline, and its underlying mechanisms. Experimental Approach: Identification of IDHP was identified by mass spectrometry, and proton and carbon nuclear magnetic resonance spectra. Myocardial collagen was quantitatively assessed with Picrosirius Red staining. Expression of mRNA for collagen was evaluated with real‐time PCR. Phosphorylated and total p38 MAPK, NADPH oxidase (NOX) and superoxide dismutase (SOD) were analysed by Western blot. Generation of reactive oxygen species (ROS) generation was evaluated by dihydroethidium (DHE) fluorescent staining. NOX2 was knocked down using specific siRNA. Key Results: IDHP attenuated β‐adrenoceptor mediated cardiac fibrosis in vivo and inhibited isoprenaline‐induced proliferation of neonatal rat cardiac fibroblasts (NRCFs) and collagen I synthesis in vitro . Phosphorylation of p38 MAPK, which is an important mediator in the pathogenesis of isoprenaline‐induced cardiac fibrosis, was inhibited by IDHP. This inhibition of phospho‐p38 by IDHP was dependent on decreased generation of ROS. These effects of IDHP were abolished in NRCFs treated with siRNA for NOX2. Conclusions and Implications: IDHP attenuated the cardiac fibrosis induced by isoprenaline through a NOX2/ROS/p38 pathway. These novel findings suggest that IDHP is a potential pharmacological candidate for the treatment of cardiac fibrosis, induced by β‐adrenoceptor agonists. Linked Articles: This article is part of a themed section on Chinese Innovation in Cardiovascular Drug Discovery. To view the other articles in this section visithttp://dx.doi.org/10.1111/bph.2015.172.issue-23